A miniature stainless steel net dumbbell-shaped stir-bar for the extraction of phthalate esters in instant noodle and rice soup samples. Issue 1 (2nd January 2020) - Sukree, Warakorn; Sooksawat, Dhassida; Kanatharana, Proespichaya; Thavarungkul, Panote; Thammakhet-Buranachai, Chongdee
Abstract: This work reports the development of a very-simple-to-construct stir-bar extraction device so called "a dumbbell-shaped stainless steel stir-bar." The extraction device was assembled from a rolled up stainless steel net filled with an XAD-2 sorbent and a metal rod to allow the use of a magnetic stirrer during extraction. The dumbbell-shaped stainless steel stir-bar was used to extract diethyl phthalate (DEP), dibutyl phthalate (DBP), and di(2-ethylhexyl) phthalate (DEHP) before analysis by a gas chromatograph equipped with an electron capture detector (GD-ECD). Under the optimal conditions, the developed method provided a good linearity from 10.0 to 1, 000.0 ng mL −1 for all three compounds. Limits of detection and limits of quantification were 9.37 ± 0.29 ng mL −1 and 31.22 ± 0.95 ng mL −1 for DEP, 5.73 ± 0.31 ng mL −1 and 19.1 ± 1.0 ng mL −1 for DBP and 3.30 ± 0.06 ng mL −1 and 11.0 ± 0.19 ng mL −1 for DEHP, respectively. Good recoveries in the range of 81.89 ± 0.17 to 109.5 ± 2.0% were achieved when the method was used to extract phthalate esters in five instant noodle and two rice soup samples.